Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Well, I got stuck in that question:

Consider the integral expression in $x$: $P = x^3+x^2+ax+1$ where $a$ is a rational number. At $a=A$ the value of $P$ is a rational number for any $x$ which satisfies the equation $x^2+2x-2=0$, and in this case the value of $P$ is $B$. Find $A$ and $B$.

I've tried to use the last equation in the first one, I multiplied it by $x$ and then I got $x^3 = 2x-2x^2$ and I put that in place of $x^3$ in $P$ and this led me to $P = -x^2+(2+a)x+1$. I thought that as $P$ is a rational number, I would choose a rational number to put in place of $P$, but I don't know if this expression includes all rational numbers. Anyway, I tried the value $P=1$ and this led me to $x=2+a$, well, this didn't help, I was trying to find $a$ and I found an $x$ that makes $P$ be $1$.

Any idea?

share|cite|improve this question
up vote 3 down vote accepted

The procedure you began works after not much more calculation. We are considering $x$ such that $x^2=2-2x$. So $x^3=2x-2x^2$.

Thus $x^3+x^2=2x-x^2=2x-(2-2x)=4x-2$.

We conclude that if $x$ is either root of the quadratic $x^2+2x-2=0$, then our original expression $x^3+x^2+ax+1$ is equal to $4x-2+ax+1$. But the roots of the quadratic are irrational, and $a$ is rational. So the only way for $4x-2+ax+1$ to be rational is if the coefficient of $x$ is $0$. Thus $A=-4$. It follows that $B=-2+1=-1$.

Remark: Or else we could do it the boring way, by solving the quadratic and substituting. The cubes and squares of the roots can be easily calculated explicitly. It would have been a better problem if it had involved powers of $x$ say up to $6$, and the quadratic had roots more complicated than $-1\pm\sqrt{3}$. Then the method we used above is not much more stressful to carry out, while substituting and expanding gets quite unpleasant.

share|cite|improve this answer
Well, if $a=-4$, then the last equation you wrote down becomes $4x-2-4x+1=0$ then $-1=0$. I think I hasn't really got your idea or it is not yet okay as answer. – Ataias Reis Sep 8 '12 at 20:55
I had a typo earlier. Did not mean $=0$, meant $4x-2+ax+1$. – André Nicolas Sep 8 '12 at 20:57
Thanks, I understood it now. – Ataias Reis Sep 8 '12 at 21:00
@AndréNicolas I can't seem to get $x^3+x^2=4x-2$, since $x^2=2-2x$. Can you please expand on that? – Secret Apr 18 '14 at 7:15
@Secret: It is all in the second and third line of the answer. From $x^2=2-2x$ we get by multiplying by $x$ that $x^3=2x-2x^2$, so $x^3+x^2=2x-x^2=2x-(2-2x)=4x-2$. – André Nicolas Apr 18 '14 at 13:14

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.